PENGEMBANGAN USAHA KELOMPOK PENGRAJIN TEMPE DESA PULO KECAMATAN REMBANG KABUPATEN REMBANG - A. Aviv Mahmudi; Rikah Rikah (Universitas YPPI Rembang, 2021)
Pulo Village also has great potential as a producer of superior regional products in Rembang Regency in the form of tempe products. The main obstacle faced by tempe producers is that the price of soybeans as the main raw material tends to continue to increase, they do not have the knowledge and ideas to further develop their business, namely the development of innovative products for processed snacks based on tempe. Other problems that arise from tempe craftsmen include problems with marketing, technology utilization, human resources problems, business management and financial administration. Product innovation is one of the main solutions to solve production problems. It is hoped that the development of product innovation can overcome the obstacles faced today, namely the decreasing margins obtained due to the increasing price of soybeans. One of the product innovations is in the form of tempeh chips using organic (natural) ingredients. Another advantage obtained from the diversification of the tempe chips product, namely the longer shelf life so that the marketing can be expanded, as well as increasing the number of workers of each tempe craftsman.Keywords: Tempe Chips, Business Management, Product Innovation, Tempe.